Management of Cervical Fibroid during the Reproductive Period - Remon Keriakos; Mark Maher (Hindawi Limited, 2013)
This is a case report of a 29-year-old lady who presented with excessive vaginal discharge and sessile cervical fibroid arising from the vaginal portion of the cervix. She was not suitable for uterine artery embolization as she has never previously been pregnant before. She was encouraged to get pregnant and to avoid surgical excision which can lead to hysterectomy. Shortly after, she became pregnant. She had many admissions during pregnancy due to bleeding from the fibroid, and in one occasion she had blood transfusions. The fibroid increased in size to become larger than the head of the baby. An emergency caesarean section was performed at 37 weeks when she attended in labour before the date of her elective caesarean section. She was managed conservatively following delivery in the hope that the fibroid becomes smaller making surgery easier. The fibroid degenerated and reduced in size. Vaginal myomectomy was carried out. The patient is now pregnant for the second time and had a cervical suture at 20 weeks gestation. In this educational case report we discuss the different management options of cervical fibroids and review the literature of other similar cases and their outcome.